Obesity and Cardiovascular Disase Risk Factors, Paradox and Impact of Weight Loss (KYAMC Journal, 2017)
Obesity has reached global epidemic proportions in both adults and children and is associated with numerous comorbidities, including hypertension (HTN), type II diabetes mellitus, dyslipidemia, obstructive sleep apnea and sleep-disordered breathing, certain cancers and major cardiovascular (CV) disease. Because of its maladaptive effects on various CV risk factors and its adverse effects on CV structure and function, obesity has a major impact on CV diseases, such as heart failure (HF), coronary heart disease (CHD), sudden cardiac death, and atrial fibrillation, and is associated with reduced overall survival. Despite this adverse association, numerous studies have documented an obesity paradox in which overweight and obese people with established CV disease, including non-obese patients. This review summarizes the adverse effects of obesity on CV disease risk factors and its role in the pathogenesis of various CV diseases, review the obesity paradox and potential explanation for these puzzling data, and concludes with a discussion regarding the current state of weight reduction in the prevention and treatment of CV diseases.KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 476-479